Development of public-private partnership in the penal system - A. P. Skiba; A. V. Rodionov; M. Yu. Voronin (Правоприменение)
The subject. The production sector of the Russian penitentiary system requires development and modernization in order to increase the level of convicts’ employment, to ensure the growth of their labor productivity, which is ultimately aimed at increasing the level of correctional impact of socially useful labour. In modern conditions of market economy development, low efficiency of state production organizations economic activity on competitive markets, as well as the lack of budget funds for the modernization of production assets, the most promising form of organization of penitentiary institutions production activities is public-private partnership. The aim of the article is to develop scientifically based provisions that define the most promising areas for the development of Russian legislation, which will significantly improve the practice of implementing public-private partnership projects in the production sector of the penitentiary system. The methodology. In the course of the study, a complex of general scientific and special methods of scientific search was used, including scientific abstraction, a systematic approach, a dialectical method of cognition, as well as comparative legal and structural-system methods of research. The information base of the study is represented by scientific works of Russian and foreign scientists-penitentiaries, statistical data, regulations, as well as data on legal practice in the field under study. The main results, scope of application. The prerequisites for promising changes in the legislation that determine the need for a significant modernization of the production sector of the penitentiary system are identified. The expansion of the practice of implementing production projects with the involvement of private business initiatives in penitentiary institutions makes it possible to strengthen the corrective impact of socially useful labour, to improve convicts’ food and clothing provision, as well as the communal living conditions of their detention. Conclusion. The article substantiates the need to develop a concept of interaction between the penitentiary system and the business community in order to improve the efficiency of convicts’ employment and their correction, within the framework of which the most relevant directions and stages of the development of public-private partnership should be determined in the future.